Design analysis of electric two wheeler frame - Vashist, Devendra; Singh, Nikhil; Tomar, Gaurang; Shadija , Aayush Shadija (PREPARE@u® | IEI Conferences, 2021)
The motorcycle frame is one of the major component. It provides vehicle rigidity and strength when the two wheeler is in motion with any road condition. It links various parts of the vehicle system and holds them together. The present study includes modelling of the frame as per structural and ergonomics considerations. The design constraints are governed by loads acting on the frame through front and rear suspension, steering, transmission system and assembly sub systems. The study includes the stress analysis of the designed frame using finite element analysis software (Autodesk fusion 360) for reduced weight without affecting structural strength. Results indicate that a reduction of 20kg (33% weight) can be achieved for a conventional available frame having 60Kg weight. This overall reduced the cost is achieved by selecting proper material and making changes in design. The designed frame can sustain a load of 300Kg / 2943N with safety factor 15.